Pelatihan Media Pembelajaran Interaktif Menggunakan Classpoint pada Guru SDN 2 Banteran - Dwi Krisbiantoro; Banu Dwi Putranto; Nourma Islam Dewi Cantika; Ismail Alfi Firmansyah; Abdul Azis (Politeknik Piksi Ganesha Indonesia, 2025)
The problem encountered in general by teachers in UPK Kec.Sumbang at this time is the limited ability of teachers to use technology-based learning media so that teachers in providing material are only limited to lecturing and telling students to do the questions in the LKS, of course this makes students feel bored and there is no interactive between students and teachers when students succeed in doing assignments or answering questions given by seeing the current state of students tend to be more interested in digitalisation. The solution that can be done is to carry out training activities for making technology-based learning media using classpoint. The technical implementation is through the provision of theoretical material, practice of making learning media, to the evaluation stage. The method used was lecture and drill practice. The stages of the activity with the delivery of material on the importance of learning media, the introduction of learning media, followed by drill practice. The results of the activity showed that 90% of teachers were able and gave a positive response to the activity and from this activity the ability of teachers to increase in the use of technology.